Kodifikasi RUU KUHP Melemahkan Komisi Pemberantasan Korupsi - larensius Arliman S (UIR Law Review, 2018)
Social phenomenon called corruption is the reality of human behavior in social interaction that is considered deviant, and endangering society and state. Corruption as a form of extraordinary crime that is very detrimental to the people, the idea to weaken the Corruption Eradication Commission (KPK), one of them by incorporating the Corruption Act (Corruption Act) and Money Laundering Criminal Act (UU TPPU) into the Draft Law of the Penal Code (RUU KUHP). Corruption greatly weakens the existence of the KPK later. Just imagine as long as the KPK, many cases that can be dismantled, the government should anticipate the weakening of this KPK, where the author tries to offer the government open the formation of other laws to regulate this. If this is implemented then there will be 3 (three) institutions that continue to oversee corruption, namely: Police, Prosecutors and KPK primarily. This is to eradicate corruption in Indonesia as soon as possible.